2012
DOI: 10.2298/pim1205083s
|View full text |Cite
|
Sign up to set email alerts
|

The exact analytical solution for the gas lubricated bearing in the slip and continuum flow regime

Abstract: The exact analytical solution for the compressible two-dimensional gas flow in the microbearing is presented. The general slip-corrected Reynolds lubrication equation is derived and it is shown that it possesses an exact analytical solution. It is obtained by a suitable transformation of the independent variable, and it provides the pressure distribution in the bearing as well as the mass flow rate through it. By neglecting the rarefaction effect, this solution is also applicable to the continuum gas flow in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…2, more extensive validation of this analytical solution was already presented in [8] by comparison of the analytically obtained results with available numerical results. Namely, the slip flow results for a wide range of Knudsen number and the continuum flow conditions, provided by the general analytical solution from this paper and [8], are in excellent agreement with Fukui and Kaneko [15] numerical solution of the Boltzmann equation.…”
Section: Analytically Exact Solution Of the Slip-corrected Reynolds Lmentioning
confidence: 85%
See 2 more Smart Citations
“…2, more extensive validation of this analytical solution was already presented in [8] by comparison of the analytically obtained results with available numerical results. Namely, the slip flow results for a wide range of Knudsen number and the continuum flow conditions, provided by the general analytical solution from this paper and [8], are in excellent agreement with Fukui and Kaneko [15] numerical solution of the Boltzmann equation.…”
Section: Analytically Exact Solution Of the Slip-corrected Reynolds Lmentioning
confidence: 85%
“…The obtained differential equation written in the form in which variables H and Π are separated (eq. 16) can be transformed in the differential equation with separated variables presented by equation (2.14) in [8]. This indicates that despite the fact that final analytical solutions obtained by transformations of the dependent and independent variable don't have the same form, the both solutions give the same result.…”
Section: Analytically Exact Solution Of the Slip-corrected Reynolds Lmentioning
confidence: 98%
See 1 more Smart Citation
“…Stevanovic et. al [ 19 ] derived general slip-corrected Reynolds lubrication equation and showed that it possesses an exact analytical solution. Wieczorek and Ivantysynova [ 20 ] developed a method to calculate non-isothermal gap flow in the connected gaps of swash plate type axial piston machines by combining Matlab and C language routines that analyzed the motion equation of all moveable parts of the rotating group and performed gap simulation of all concerned gaps.…”
Section: A Short Description Of Axial Piston Pumpsmentioning
confidence: 99%
“…The knowledge of explicit exact solutions of the nonlinear PDE is very useful for the qualitative analysis [14]. The obtained analytical solution can be usefully applied for testing the other, experimental or numerical results for adequate modeling of modern technologies [15].…”
Section: Introductionmentioning
confidence: 99%